VD_FINDINFO Décision / 2013 / 592 vom 18. Juni 2013 - VD Tribunal cantonal (2013)
NE BIS IN IDEM, NON-LIEU, CHOSE JUGÉE, FRAISEN GÉNÉRAL, PROCÉDÉ TÉMÉRAIRE | 11 CPP (CH), 310 CPP (CH), 323 CPP (CH), 427 al. 2 CPP (CH)